2012
DOI: 10.11594/jtls.02.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity Studies of Brucea javanica Merril Leaves Extract on Mice

Abstract: The objective of the study was to evaluate the oral acute toxicity of Brucea javanica Merril extract on both Male and Female DDY-Mice. Brucea javanica leaves function as a cytotoxic, anti-diarrhoea, etc. Brucea javanica leaves extract was administered orally for the first 24 hours at various dose levels (562.5 mg/kg bw (body weight), 1125 mg/kg bw, 2250 mg/kg bw, and 4500 mg/kg bw) to determine the toxicity effects. The treatment groups were compared to the normal control. Vital organs (liver, heart, lymph, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…collected in Indonesia on mice was previously reported [38]. In this investigation, it was reported that vital organs and body average weights of treated leaves ethanol extract did not show no difference compared to control group.…”
Section: Acute Toxicity Of the Aqueous Extract Of B Sumatrana Leavesmentioning
confidence: 57%
“…collected in Indonesia on mice was previously reported [38]. In this investigation, it was reported that vital organs and body average weights of treated leaves ethanol extract did not show no difference compared to control group.…”
Section: Acute Toxicity Of the Aqueous Extract Of B Sumatrana Leavesmentioning
confidence: 57%
“…Other studies also have a similar result, IC 50 of BrD in non-tumorigenic hepatocyte and pancreatic progenitor cells is more than 250 µM [ 41 ] and over 30 µM in normal skin fibroblast [ 42 ]. A study about the acute cytotoxicity of oral administration of Brucea javanica fruit also shows mild cytotoxicity and safe to be used as plant medicine [ 44 ], and administration of high dose BrD (3 mg/kg) in mice was associated with no obvious toxicity [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rats treated with P. minima water extract continued to gain weight throughout the 14 days of experiment. According to Angelina et al (2012), the alteration of body weight gain and organ weights of the treatment groups compared to the control group will reflect the toxicity of the substance 19 . In this study, there were no significance differences in body weight gain with control group in the result analysis in p≥0.05.…”
Section: Discussionmentioning
confidence: 99%